2001
DOI: 10.1086/mre.16.4.42629339
|View full text |Cite
|
Sign up to set email alerts
|

Fishing Skill in Developing Country Fisheries: The Kedah, Malaysia Trawl Fishery

Abstract: The question arises for fishery managers as to whether or not there are observable and measurable attributes of the skipper or vessel that fishery managers can monitor and possibly regulate to control expansions in fishing capacity from this source. This paper addresses this neglected issue of resource management through a case study of the trawler fishery in the state of Kedah in Peninsular Malaysia. In the Kedah trawl fishery, skipper characteristics other than ethnicity did not significantly affect technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 37 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…This means that some vessels use a little more labour than the level that maximizes annual gross revenue of the vessel. Viswanathan et al (2002) also found this in the case of the Malaysia trawl fishery. A possible explanation is the abundant labour force in developing countries such as Vietnam.…”
Section: Empirical Results and Discussionmentioning
confidence: 66%
“…This means that some vessels use a little more labour than the level that maximizes annual gross revenue of the vessel. Viswanathan et al (2002) also found this in the case of the Malaysia trawl fishery. A possible explanation is the abundant labour force in developing countries such as Vietnam.…”
Section: Empirical Results and Discussionmentioning
confidence: 66%
“…From the vantage of the entire fishery, the marginal benefits from cutting back on harvest-the ARTICLE IN PRESS 9 This technical description has an analogous relationship to the prototypical model of the polluting firm [5]. Note, as well, that by presuming a homogeneous technology for all fishermen, we are ignoring real-world variations in the production technologies of fishermen [10,20,24]. Alterations to accommodate such variations are relatively straightforward for the case of a discrete number of efficiency classes.…”
Section: Article In Pressmentioning
confidence: 99%
“…1 Currently, there are two primary methods used to estimate fishery production technologies: data envelope analysis (DEA) [21,19,30] and stochastic production frontier (SPF) models [31,10,39,15,22]. DEA does not assume a parametric form for the production technology and is therefore a more general and flexible model.…”
Section: Introductionmentioning
confidence: 99%